2009
DOI: 10.1136/jnnp.2009.183517
|View full text |Cite
|
Sign up to set email alerts
|

Bulbar involvement in patients with antiganglioside antibodies against NeuNAc( 2-3)Gal

Abstract: Reactivity against the NeuNAc(alpha2-3)Gal epitope is rare and is generally found in association with reactivity against the disialosyl epitope. It can be detected in patients with acute or chronic disorders and could be a serological marker of clinical bulbar involvement and, to a lesser extent, associated with the development of severe respiratory failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 20 publications
2
7
0
Order By: Relevance
“…Reactivity against GM3 but not against GD1a was detected in two other patients, suggesting a partial cross-reactivity against the epitope NeuNAc(alfa2-3)Gal. This spectrum of reactivity has been reported in a patient with acute relapsing sensory ataxic neuropathy (Rojas-Garcia et al, 2008b), acute sensory ataxic neuropathy (Rojas-Garcia et al, 2010), and chronic sensory ataxic neuropathy with antidisialosyl antibodies Rojas-Garcia et al, 2010). All these data suggest that in some cases ataxia could be related to a wider spectrum of reactivity and not limited to GD1b or other disialylated structures.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…Reactivity against GM3 but not against GD1a was detected in two other patients, suggesting a partial cross-reactivity against the epitope NeuNAc(alfa2-3)Gal. This spectrum of reactivity has been reported in a patient with acute relapsing sensory ataxic neuropathy (Rojas-Garcia et al, 2008b), acute sensory ataxic neuropathy (Rojas-Garcia et al, 2010), and chronic sensory ataxic neuropathy with antidisialosyl antibodies Rojas-Garcia et al, 2010). All these data suggest that in some cases ataxia could be related to a wider spectrum of reactivity and not limited to GD1b or other disialylated structures.…”
Section: Discussionsupporting
confidence: 70%
“…The most frequent additional reactivity was against GM3 in patients 1–4. In two of them, cases 2 and 4, that have been reported elsewhere ( Rojas‐Garcia et al, 2010 ) , ELISA identified simultaneous reactivity against GM3, GT1b, and GD1a gangliosides, suggesting binding specificity for terminal NeuNAc( α 2‐3)Gal cross‐reactivity (Fig. 1).…”
Section: Resultssupporting
confidence: 54%
See 1 more Smart Citation
“…The whole reactivity cannot be explained by a single antibody, but it is similar to other reported cases. 2,7,10 An IgM monoclonal protein kappa light chain type was detected, and the reactivity to gangliosides corresponded to the same kappa light chain. Cold agglutinins were not tested.…”
mentioning
confidence: 95%
“…Case studies have shown that association of early bulbar palsy with Guillain-Barre Syndrome and preceding history of respiratory symptoms in Anti GM-3 and Anti GT-1b positive patients and Anti GT-1a positive patients [8,9]. But this test is much expensive and not available in our hospital, so it could not be done.…”
Section: Postulated Immunopathogenesis Of Guillain Barre Syndrome: [5]mentioning
confidence: 98%